PERAN DESA WISATA TERHADAP KESEJAHTERAAN PEKERJA PARIWISATA DI DESA WISATA BEJIHARJO KECAMATAN KARANGMOJO KABUPATEN GUNUNGKIDUL - , MITA WAHYUNITA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Bejiharjo Tourist Village is included in development of ecotourism with involving local communities as tourism businesses. The purposes of this study are (1) to describe the developments of Bejiharjo Village during a tourist village and (2) to analyze the improvement of the welfare workers because of the presence a tourist village. This study use survey method to collected primary data were collected through observation and interview with respondents using a questionnaire. Sampling studies using mutlistage sampling. The number of respondents are 50 peoples with unit of analysis is household. Technique of analysis are using SWOT analysis and descriptive statistical analysis. The result are (1) the development of Bejiharjo Village during a Bejiharjo Tourist Village marked by the success of managing object tourist attraction that can be seen from the addition of the secretariat of tourism every years. (2) Enchanced welfare worker of tourist because of the presence a family, increase the variety of jobs, increase knowledge in the field of tourism business management, the establishment of social interaction between residents and the last is participation of women and older age groups. Keywords: Tourist Village, Welfare Society, Tourism Business, Community Empowerment.